The Psychology of Grey in Painting Backgrounds - Roslan, Aimi Atikah; Taharuddin, Nurul Shima; Nazrin, Nizar (Idealogy Journal, 2022)
This writing is about a study of the psychology of the colour Gray used on the painting backgrounds. The study concerns how the colour Gray affects the behaviour of artists and has an impact on the production of works of art. A descriptive research using qualitative research method through surveys and observations as instrument. The artist uses the colour Gray as his guide in producing works to give a sense of emotional strength, feelings of melancholy, passion and so on. Each colour has a different psychological and emotional effect. Keywords: Psychology, Colour Gray, Painting